Alternativas de manejo para la araña roja (Tetranychus urticae), en el cultivo de cáñamo (Cannabis sativa). - Jiménez Lara, Alex Daniel (2022)
Hemp is an annual plant that in recent years is having an impact due to its usefulness for the textile, medicinal and food industries. However, it presents a great problem due to Tetranychus urticae, this being a pest capable of greatly reducing production and, in turn, the quality of Cannabis sativa. The objective is to identify the best alternative for the management of the red spider in hemp cultivation. Based on the analysis, the compilation of information on cultural, biological and chemical methods, it is possible to conclude that the best alternative for the control of the red spider is biological control with the mite Neoseiulus californicus, followed by the mite Phytoseiulus persimilis. Chemical control is commonly used by producers, but many times due to lack of knowledge they use product molecules repetitively and/or in inappropriate doses, thus eradicating the beneficial insects of this pest and causing it to become more resistant to pests. chemical products.